Adverbials : the interplay between meaning, context, and syntactic structure - Austin, Jennifer R.; Engelberg, Stefan; Rauh, Gisa (Linguistik aktuell, 2004)
Adverbials have become an important testing ground for research on the interfaces between syntax, semantics, and pragmatics. The articles selected for this volume present recent research on this topic. Among the issues addressed are the occurrence of adverbials in various domains of the sentence Mittelfeld, left and right periphery, adverbials in front of gaps, and the influence of the discourse context on the interpretation and position of adverbials. Particular classes of adverbials that are discussed include domain, locative, temporal, manner, transparent, and degree adverbials. Beyond the.